The Analysis of Maratua Island Tour Package as a Main Destination in PT. KAKABAN TRIP - Pranoto, Mazayahalwa Erta (UI Scholars Hub, 2024)
ABSTRACT Indonesia is an archipelagic country that has many marine tourism destinations. One of the most popular marine tourism is Maratua. This study aims to find out what are the attractions of Maratua that make Maratua the most popular tour. In addition, it also aims to find out the marketing strategy and constraints on the Maratua tour package. The research method used is qualitative research with data collection techniques, namely observation, interviews, and literature studies. The results of this study reveal that the main attraction in Maratua is the marine biota and its resorts which are similar to the Maldives. The marketing strategy used onKakaban Trip is using the 4P concept (product, price, place, and promotion). The products sold at Kakaban Trip are tour packages for eastern Indonesia, prices vary because there are open trip, private trip, and honeymoon prices. Places to carry out this business are in Jakarta and Balikpapan. The promotion is carried out by focusing on social media. Meanwhile, the obstacle in the Maratua trip package is transportation to the destination